MHMIC Six-port Interferometer for W-band Transceivers: Design and Characterization - Emilia Moldovan; Nazih Khaddaj Mallat; Serioja Ovidiu Tatu (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The study has presented an extensive analysis of an integrated millimeter wave six-port interferometer, operating over a 10 GHz band, from 80 to 90 GHz. It has covered both semi-unlicensed point-to-point links (81-86 GHz), and imaging sensor system frequencies (above 85 GHz). An in-house process is used to fabricate miniaturized hybrid millimeter wave integrated circuits on a very thin ceramic substrate. Two-port S-parameter measurements are performed on a minimum number of circuits integrated on the same die, exploiting the circuit’s physical symmetry and chosen to collect enough data for full-port characterization. Based on these measurements on an integrated prototype, a six-port circuit computer model implemented and advanced system simulations performed for circuit analysis. Interferometer performances evaluated using several methods: analysis of harmonic balance, qi points’, homodyne quadrature demodulation, and error vector modulation (EVM). The analysis showed that this circuit can directly perform, without any calibration, the demodulation of various PSK and QAM signals over the 10 GHz band, with very good results.